Pengendalian Waktu Pembangunan Jalan Poros Desa Ruas Kedungprahu- Sukowiyono - Lyya Supriyono; Laily Fatmawati (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2020)
Abstract— The road is a vital tool for the village community where the majority of their livelihood is as a farmer. Increasing the economy in the village is not only determined from agricultural yields but also determined by supporting facilities and infrastructure such as road repair. The road construction process with a long duration of time will certainly hamper the performance of the farmers which has an impact on declining income. Therefore it is necessary to control the working time on the Construction of the Village Axis Road Kedungprahu-Sukowiyono so that work can be completed as quickly as possible without reducing the quality of road pavement work. In this study we use the CPM (Critical Parth Method) method in evaluating the scheduling of the Kedungprahu-Sukowiyono road segment construction project. With the CPM (Critical Parth Method) Method we can find out the critical paths and non-critical paths. The results of the study of controlling the time of construction of the village road axis of the Kedungprahu-Sukowiyono section were accelerated on the critical path. Savings of funds amounted to 1,723,879.68, there was no change in the critical path after accelerating the project with the addition of overtime hours, the implementation time from 60 days to 55 days. Keywords—: Time control; road; kedungprahu.